2007
DOI: 10.1002/ar.20611
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 9 (AQP9) Localization in the Adult Dog Testis Excurrent Ducts by Immunohistochemistry

Abstract: Aquaporins (AQPs) are small, intrinsic membrane proteins that are present in many cell types involved in fluid transport. AQP9 is a major apical water channel that is expressed throughout the efferent ducts, epididymis, and vas deferens, as well as in other regions of the human and rodent male reproductive tract. The target of this study was to examine the expression of AQP9 in epithelial cells in the adult dog efferent ducts, epididymis, and vas deferens. Samples of dog male reproductive tract comprising frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 31 publications
5
31
5
Order By: Relevance
“…AQP9 is strongly expressed in the plasma membranes of Leydig cells in rat testis and adult dog testis. Studies showed that AQP9 may be involved in the early stages of spermatogenesis and in the secretion of tubule liquid [32,33]. RNF6 (ring finger protein 6) is predicted by hsa-miR-181d and show increased expression during meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…AQP9 is strongly expressed in the plasma membranes of Leydig cells in rat testis and adult dog testis. Studies showed that AQP9 may be involved in the early stages of spermatogenesis and in the secretion of tubule liquid [32,33]. RNF6 (ring finger protein 6) is predicted by hsa-miR-181d and show increased expression during meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have identified more than 10 different types of AQPs in mammals, found in several organs of different species, such as human kidney (Deen et al, 1994), rat epithelial tissue (Lindsay and Murphy, 2007), human blood vessels (Agre and Kozono, 2003), reproductive system of rodents (McConnell et al, 2002), dogs (Domeniconi et al, 2007), and pigs (Skowronski et al, 2009). The studies with AQP1 demonstrated that these proteins are small and integral membrane protein types, crossing the membrane from side to side, and containing two semipores that together form a water channel (Verkman and Mitra, 2000), assisting the transport of solutes (Thoroddsen et al, 2011).…”
Section: Aquaporinsmentioning
confidence: 99%
“…This same protein was expressed in the endolymphatic sac in the ear in humans, suggesting an active role in the homeostasis of the endolymph (Ishibashi, 2009). AQP2 was also found in the rete testis, efferent ducts, and epididymis of dogs, although its functional role in the reproductive tract is still unknown (Domeniconi et al, 2007).…”
Section: Main Types and Functions Of Aquaporinsmentioning
confidence: 99%
See 2 more Smart Citations